Conservation and planning - Dobby, Alan. (London, United Kingdom : Hutchinson of London, 1978)
The contents are focused at students of the environment, whether practitioners, consumers or general readers. It is hoped that what follows, a combination of compilation, chronicle and criticism which brings together facts and opinions only found in disparate sources, may with the interpretations contribute to an understanding of the development of conservation so far.
Part One. The concept and its development -- Part Two. Practical considerations -- Appendices -- Index.
Includes index.
Keywords: CONSERVATION -- PLANNING